Characterization of CIPK Family in Asian Pear (Pyrus bretschneideri Rehd) and Co-expression Analysis Related to Salt and Osmotic Stress Responses - Tang, Jun; Lin, Jing; Li, Hui; Li, Xiaogang; Yang, Qingsong; Cheng, Zong-Ming; Chang, Youhong (Frontiers in Plant Science, 2016)
Asian pear (Pyrus bretschneideri) is one of the most important fruit crops in the world, and its growth and productivity are frequently affected by abiotic stresses. Calcineurin B-like interacting protein kinases (CIPKs) as caladium-sensor protein kinases interact with Ca2+-binding CBLs to extensively mediate abiotic stress responses in plants. Although the pear genome sequence has been released, little information is available about the CIPK genes in pear, especially in response to salt and osmotic stresses. In this study, we systematically identified 28 CIPK family members from the sequenced pear genome and analyzed their organization, phylogeny, gene structure, protein motif, and synteny duplication divergences. Most duplicated PbCIPKs underwent purifying selection, and their evolutionary divergences accompanied with the pear whole genome duplication. We also investigated stress -responsive expression patterns and co-expression networks of CIPK family under salt and osmotic stresses, and the distribution of stress-related cis-regulatory elements in promoter regions. Our results suggest that most PbCIPKs could play important roles in the abiotic stress responses. Some PbCIPKs, such as PbCIPK22, -19, -18, -15, -8, and -6 can serve as core regulators in response to salt and osmotic stresses based on co-expression networks of PbCIPKs. Some sets of genes that were involved in response to salt did not overlap with those in response to osmotic responses, suggesting the sub-functionalization of CIPK genes in stress responses. This study revealed some candidate genes that play roles in early responses to salt and osmotic stress for further characterization of abiotic stress responses medicated by CIPKs in pear.